Zinc ions bind to and inhibit activated protein C - Zhu, Tianqing; Ubhayasekera, Wimal; Nickolaus, Noëlle; Sun, Wei; Tingsborg, Susanne; Mowbray, Sherry L.; Schedin-Weiss, Sophia (Thrombosis and Haemostasis, 2010)
Zn2+ ions were found to efficiently inhibit activated protein C (APC), suggesting a potential regulatory function for such inhibition. APC activity assays employing a chromogenic peptide substrate demonstrated that the inhibition was reversible and the apparent KI was 13 ± 2 μM. kcat was seven fold decreased whereas KM was unaffected in the presence of 10 μM Zn2+. The inhibitory effect of Zn2+ on APC activity was also observed when factor Va was used as a substrate in an assay coupled to a prothrombinase assay. The interaction of Zn2+ with APC was accompanied by a reversible ~40% decrease in tryptophan fluorescence, consistent with the ion inducing a conformational change in the protein. The apparent KD was 7.4 ± 1.5 μM and thus correlated well with the apparent KI. In the presence of physiological Ca2+ concentration the KI and KD values were three to four fold enhanced, presum-ably due to the Ca2+-induced conformational change affecting the conformation of the Zn2+-binding site. The inhibition mechanism was non-competitive both in the absence and presence of Ca2+. Comparisons of sequences and structures suggested several possible sites for zinc binding. The magnitude of the apparent KI in relation to the blood and platelet concentrations of Zn2+ supports a physiological role for this ion in the regulation of anticoagulant activity of APC. These findings broaden the understanding of this versatile serine protease and enable the future development of potentially more efficient anticoagulant APC variants for treatments of thrombotic diseases.
Keywords: Activated protein C; serine protease; zinc; blood coagulation; enzyme inhibition